2016
DOI: 10.1128/jvi.01465-16
|View full text |Cite
|
Sign up to set email alerts
|

Tetherin Antagonism by HIV-1 Group M Nef Proteins

Abstract: Although Nef is the viral gene product used by most simian immunodeficiency viruses to overcome restriction by tetherin, this activity was acquired by the Vpu protein of HIV-1 group M due to the absence of sequences in human tetherin that confer susceptibility to Nef. Thus, it is widely accepted that HIV-1 group M uses Vpu instead of Nef to counteract tetherin. Challenging this paradigm, we identified Nef alleles of HIV-1 group M isolates with significant activity against human tetherin. These Nef proteins pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Instead, we show that both Nand C-terminal domains in AD8 Nef contribute to the reduction in the cell surface levels of human tetherin ( Figure 5). Anti-tetherin activity has been reported for several M group subtype C HIV-1 Nef proteins [42]. In agreement with our findings, these Nef proteins downregulated cell surface l-tetherin, which correlated with enhanced virus release and replication.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Instead, we show that both Nand C-terminal domains in AD8 Nef contribute to the reduction in the cell surface levels of human tetherin ( Figure 5). Anti-tetherin activity has been reported for several M group subtype C HIV-1 Nef proteins [42]. In agreement with our findings, these Nef proteins downregulated cell surface l-tetherin, which correlated with enhanced virus release and replication.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, 1.24% of primary isolates in the HIV database encode a Vpu start codon mutation [45]; it will be intriguing to investigate whether some of these viruses use their Nef proteins to overcome tetherin restriction. Interestingly, Arias et al observed that in viral strains with Nef anti-tetherin activity, the corresponding Vpu proteins displayed diminished or no anti-tetherin activity [42]. In conclusion, HIV-1 viruses appear to have retained some flexibility to use either Vpu and/or Nef to antagonize tetherin, thus ensuring that by one mechanism or another, the virus is able to antagonise this key restriction factor.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the Nef proteins of HIV-1 group O and most SIV strains are capable of counteracting tetherin by downregulating or sequestrating this antiviral protein, thereby enhancing lentiviral particle release (45)(46)(47)(48). Recently, the Nef proteins of some HIV-1 M group strains were also shown to counteract tetherin (49). Here, we provide evidence that the Nef proteins of primate lentiviruses are capable of overcoming the inhibitory effect of TIM proteins on the release of HIV-1, HIV-2, and SIVs.…”
Section: Discussionmentioning
confidence: 99%
“…The transmembrane protein SARS‐CoV ORF7a has been shown to counteract BST2 tethering by interfering with BST2 glycosylation . In addition to the likelihood that BST2‐associated restriction of SARS‐CoV virion release is mitigated by SARS‐CoV S, it is possible that a number of enveloped viruses have developed supplementary anti‐BST2 factors over time—note that in addition to Vpu, HIV‐1 Nef is capable of overcoming BST2 restrictions on virus release under certain conditions . SIV Nef and Env are capable of antagonizing BST2, and influenza neuraminidase and M2 proteins both possess anti‐BST2 capabilities.…”
Section: Discussionmentioning
confidence: 99%